Tyres and wheels. Tyres. Industrial vehicle tyres. Specification for pneumatic tyres (metric series) on 5° tapered or flat base rims: designation, dimensions and marking Part 1.5.2, (15th February 1994) - British Standards Institution,
No abstract available